MCP-1 levels in astrocyte-derived exosomes are changed in preclinical stage of Alzheimer's disease - Wang, Ting; Yao, Yunxia; Han, Chao; Li, Taoran; Du, Wenying; Xue, Jinhua; Han, Ying; Cai, Yanning (Frontiers in Neurology, 2023)
Background Alzheimer's disease (AD) is the most common form of dementia in older adults. There is accumulating evidence that inflammatory processes play a critical role in AD pathogenesis. In this study, we investigated whether inflammatory factors in plasma and astrocyte-derived exosomes (ADEs) from plasma are differentially expressed in the early stages of AD and their potential role in pathological processes in the AD continuum. Method We included 39 normal controls (NCs), 43 participants with subjective cognitive decline (SCD), and 43 participants with amnestic mild cognitive impairment (aMCI)/AD. IL-6, IL-8, and MCP-1 in plasma and ADEs from plasma were evaluated using a commercial multiplex Luminex-based kit. Results Pairwise comparisons between the groups showed no significant differences in plasma levels of IL-6, IL-8, or MCP-1. However, ADEs in the SCD group showed an increase in MCP-1 levels compared to the NC group. To differentiate the preclinical group, discriminant analysis was performed using sex, age, years of education, and genotype. This revealed a difference between the SCD and NC groups (area under the curve: 0.664). A Spearman correlation analysis of MCP-1 in plasma and ADEs showed no or weak correlation in the SCD (R = 0.150, p = 0.350) and aMCI/AD (R = 0.310, p = 0.041) groups, while a positive correlation in the NC group (R = 0.360, p = 0.026). Conclusion Plasma IL-6, IL-8, and MCP-1 levels were not significantly different. However, the concentration of MCP-1 in ADEs is slightly altered during the preclinical phase of AD, which could be a potential role of the central neuron system (CNS) immune response in the AD continuum. Clinical trial registration www.ClinicalTrials.gov, identifier: NCT03370744.